Source credibility in Nestlé’s breakfast cereal anthropomorphic mascots / Azahar Harun … [et al.] - Harun, Azahar; Samsuriv, Norsharina; Mohd Fadil, Mohd Zaki; Naseri, Roszi Nazariah Nasni; Cheng, Siew Beh (Universiti Teknologi MARA, 2020)
An anthropomorphic mascot is one of the marketing communication agents commonly found on breakfast cereal boxes. Many studies have argued that anthropomorphic mascots could enhance the brand appeal, purchase encouragement and brand loyalty. In this study, three specimens, Nestlé’s Koko Krunch, Nestle’s Honey Star and Nestle’s Cookie Crisp were chosen. The objective was to examine each of the specimens and establish understanding regarding their significance in relation to source credibility. In order to achieve this, we employed Qualitative Content Analysis (QCA). Prior to that, two raters examined the specimens using the Source Credibility Scale (SCS) model which includes Attractiveness, Trustworthiness and Perceived Similarity. The data was processed using Inter-Rater Reliability (IRR) calculator to determine the reliability of the qualitative enquiry process. The finding shows that all specimens feature anthropomorphic characters based on animals that are not native to Malaysia. Despite this, the specimens can attract attention and promote active living. This study concludes that the Nestle breakfast cereals anthropomorphic mascots are dependent largely on the source credibility factors (Attractiveness, Trustworthiness and Similarity) which are essential for capturing attention, product arousal, purchase encouragement and purchase decision.